The Potential of Small Molecules to Modulate the Mitochondria–Endoplasmic Reticulum Interplay in Alzheimer’s Disease - Dentoni, Giacomo; Castro-Aldrete, Laura; Naia, Luana; Ankarcrona, Maria (Frontiers in Cell and Developmental Biology, 2022)
Alzheimer's disease (AD) is the most common neurodegenerative disease affecting a growing number of elderly individuals. No disease-modifying drugs have yet been identified despite over 30 years of research on the topic, showing the need for further research on this multifactorial disease. In addition to the accumulation of amyloid β-peptide (Aβ) and hyperphosphorylated tau (p-tau) several other alterations have been associated with AD such as calcium (Ca2+) signaling, glucose-, fatty acid-, cholesterol- and phospholipid- metabolism, inflammation, and mitochondrial dysfunction. Interestingly, all these processes have been associated with the mitochondria-endoplasmic reticulum (ER) contact sites (MERCS) signaling hub. We and others have hypothesized that dysregulated MERCS function may be one of the main pathogenic pathways driving AD pathology. Due to the variety of biological processes overseen at MERCS, we believe that they constitute unique therapeutic targets to boost neuronal function and recover neuronal homeostasis. Thus, developing molecules with the capacity to correct and/or modulate MERCS interplay can unleash unique therapeutic opportunities for AD. The potential pharmacological intervention using MERCS-modulators in different models of AD is currently under investigation. Here we survey small molecules with the potential to modulate MERCS structure and function and restore neuronal homeostasis in AD. We will focus on recently reported examples and provide an overview of the current challenges and future perspectives to develop MERCS-modulators in the context of translational research.